Regiospecific and stereoselective hydroxylation of 1-indanone and 2-indanone by naphthalene dioxygenase and toluene dioxygenase. - Resnick, S M (1994)
The biotransformation of 1-indanone and 2-indanone to hydroxyindanones was examined with bacterial strains expressing naphthalene dioxygenase (NDO) and toluene dioxygenase (TDO) as well as with purified enzyme components. Pseudomonas sp. strain 9816/11 cells, expressing NDO, oxidized 1-indanone to a mixture of 3-hydroxy-1-indanone (91%) and 2-hydroxy-1-indanone (9%). The (R)-3-hydroxy-1-indanone was formed in 62% enantiomeric excess (ee) (R:S, 81:19), while the 2-hydroxy-1-indanone was racemic. The same cells also formed 2-hydroxy-1-indanone from 2-indanone. Purified NDO components oxidized 1-indanone and 2-indanone to the same products produced by strain 9816/11. P. putida F39/D cells, expressing TDO, oxidized 2-indanone to (S)-2-hydroxy-1-indanone of 76% ee (R:S, 12:88) but did not oxidize 1-indanone efficiently. Purified TDO components also oxidized 2-indanone to (S)-2-hydroxy-1-indanone of 90% ee (R:S, 5:95) and failed to oxidize 1-indanone. Oxidation of 1- and 2-indanone in the presence of [18O]oxygen indicated that the hydroxyindanones were formed by the incorporation of a single atom of molecular oxygen (monooxygenation) rather than by the dioxygenation of enol tautomers of the ketone substrates. As alternatives to chemical synthesis, these biotransformations represent direct routes to 3-hydroxy-1-indanone and 2-hydroxy-1-indanone as the major products from 1-indanone and 2-indanone, respectively.